ADVANCED OXIDATIVE PROCESSES IN THE TREATMENT OF WASTEWATER: MECHANISTIC POSSIBILITIES IN POLLUTANT DEGRADATION - Ramos, J. L.; Godoy, G. B.; Monteiro, J. O. F.; Godoi, I. R. G.; Bega, B. S.; Amâncio, I. S.; Pereira, A. B. P.; Dias, P. H.; Souza, D. S. S.; Gabriel, L.; Dias, A. B.; Pires, A. M. R.; et al. (Revista Brasileira de Engenharia de Biossistemas, 2020)
This work aimed to present mechanistic studies of the main Advanced Oxidative Processes (AOPs) and some results, demonstrating the efficiency of the technology in the treatment of wastewater. AOPs are techniques capable of generating the hydroxyl radical in situ, which attributes enormous efficiency in the degradation of several recalcitrant compounds to conventional methods. This effect is due to the fact that this chemical species has a high oxidation potential, being able to degrade organic materials such as organonitrogenated, organohalogenated compounds and oxidize toxic metals, enabling the removal of this class of pollutant by filtration or precipitation. The study shows some results of the use of photocatalytic, electrochemical and photoelectrochemical processes in the treatment of wastewater known to be resistant to the main technologies of conventional treatments, providing excellent results in the discoloration of sanitary landfill leachate, textile effluents and effluent from the first alkaline extraction (E1) production of paper and cellulose. AOPs can offer viable options to remedy environmental problems, considerably reducing pollution, in addition to the great versatility to adapt to the treatment of various aqueous effluents.